Evaluation of Potential Sex Differences in the Subjective and Analgesic Effects of Morphine in Normal, Healthy Volunteers - Comer, Sandra D (2009)
RATIONALE: Sex differences in the analgesic effects of mu-opioid agonists have been documented extensively in rodents and, to a lesser extent, in non-human primates. To date, there have been few experimental studies investigating this effect in humans, and the conclusions have been equivocal. OBJECTIVES: The aims of the present study were to examine potential sex differences in the analgesic, subjective, performance, and physiological effects of morphine in human research volunteers. METHODS: Using a double-blind outpatient procedure, the present study investigated the effects of intramuscular morphine (0, 5, and 10 mg/70 kg, i.m.) in men (N=8) and women (N=10). The primary dependent measure was analgesia, as assessed by the cold-pressor and mechanical-pressure tests. Secondary dependent measures included subjective, performance, and physiological effects of morphine, as well as plasma levels of morphine. RESULTS: No differences in the analgesic and performance effects of morphine were observed between men and women, but significant differences in morphine’s subjective effects were found. Specifically, men reported greater positive effects whereas women reported greater negative effects after morphine administration. CONCLUSIONS: These data suggest that in humans, there are sex differences in the subjective mood altering effects of morphine but, based on this limited sample, there is little evidence for sex differences in its analgesic effects.